The The implementation of CSR in the extractive industries in Indonesia: What is the government’s role? - Chawa, Anif Fatma (Technium Social Sciences Journal, 2021)
This article aims to illustrate the role of government in the implementation of CSR in the extractive industries. The extractive industries need support from the government to resolve various problems which have emerged in conducting their CSR. These problems have arisen because of the contradiction and tension in the role or framework of business communities of the extractive industries, as an economic and social agent. To address those problems, based on a structural functional perspective, the extractive industries need other institution primarily government to establish policies or regulations in conducting their CSR. This study employs systemic review method reviewing 70 journal articles of research studies which focus on the implementation of CSR in the extractive industries in Indonesia. This study found that government has an important role to stipulate several regulations mostly at a national level. The regulations require the extractive industries to implement CSR to specifically address various negative impacts, socially, culturally and environmentally, on the affected communities. This study, however, also found that there is insufficient guideline at a local level in relation to CSR. Consequently, the extractive industries have no guidelines in how to establish their CSR activities, to what extend they should involve the local communities as well as the local governments in these activities and to address various problems which have emerged in the implementation of CSR. The lack of guidelines has also given rise to the different perception of the local governments on how they should be involved in the implementation of CSR.